1971
DOI: 10.1001/archpedi.1971.02110010116024
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Asymmetry and Diploid-Triploid Mosaicism

Abstract: A 9\m=1/2\-year-oldgirl with congenital asymmetry manifested by a larger right half of the body demonstrated diploid-triploid mosaicism of chromosomes from skin fibroblast cultures but normal leukocyte karyotypes. Mosaicism was found in cells from both the larger and smaller sides of her body. The association of congenital asymmetry and diploid-triploid mosaicism has been reported only twice but may be more common than previously recognized.Congeni tal asymmetry as a rec¬ ognizable clinical problem ap¬ pears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In (2n/3n) mixoploidy, the abnormal cell line has 69 chromosomes, whereas in (2d4n) mixoploidy the chromosome complement of the abnormal line is 92. We review the literature on 2d4n mixoploidy and report 2 female long-term survivors who had mental retardation and minor anomalies, some being similar to those reported in 2d3n mixoploidy [Ferrier et al, 1964;Donnai et al, 1986;Jenkins et al, 1971;Graham et al, 1981;Tharapel et al, 1983;Wulfsberg et al, 19911. These anomalies include severe intellectual handicap, digital anomalies, reduced peripheral limb muscle bulk, growth asymmetry, truncal obesity, and skin pigmentary dysplasia.…”
Section: Introductionmentioning
confidence: 73%
“…In (2n/3n) mixoploidy, the abnormal cell line has 69 chromosomes, whereas in (2d4n) mixoploidy the chromosome complement of the abnormal line is 92. We review the literature on 2d4n mixoploidy and report 2 female long-term survivors who had mental retardation and minor anomalies, some being similar to those reported in 2d3n mixoploidy [Ferrier et al, 1964;Donnai et al, 1986;Jenkins et al, 1971;Graham et al, 1981;Tharapel et al, 1983;Wulfsberg et al, 19911. These anomalies include severe intellectual handicap, digital anomalies, reduced peripheral limb muscle bulk, growth asymmetry, truncal obesity, and skin pigmentary dysplasia.…”
Section: Introductionmentioning
confidence: 73%
“…He found normal 46,XX chromosomes. Jenkins et al [1971] reported an association between congenital asymmetry and chromosomal mosaicism, but no cause-effect relationship has been established, and this association is not limited to RSS patients. The other possibility for mosaicism would be a point mutation which occurred after the splitting of the zygote into twins.…”
Section: Discussionmentioning
confidence: 98%
“…The fi nding of diploid/triploid chimeras (e.g., Van den Berghe and Verresen 1970 ) was taken as evidence that fertilization of a large polar body (common in mice) produced such abnormal individuals (dispermic chimeras). Other proposed mechanisms, such as secondary nondisjunction of whole haploid sets (Jenkins et al 1971 ) , are much less likely. De la Chapelle et al ( 1974 ) have suggested, as did other investigators, that early fusion of two embryos may be the way that whole-body chimeras are produced spontaneously, much as in the experimental model.…”
Section: Whole-body Chimerismmentioning
confidence: 99%